Global prevalence of long-term neurodevelopmental impairment following extremely preterm birth: a systematic literature review. Issue 7 (July 2021) - Sarda, Sujata P.; Sarri, Grammati; Siffel, Csaba
Objective: Neurodevelopmental impairment (NDI) is a major complication of extreme prematurity. This systematic review was conducted to summarize the worldwide long-term prevalence of NDI associated with extreme prematurity. Methods: Embase and MEDLINE databases were searched for epidemiologic and observational/real-world studies, published in English between 2011 and 2016, reporting long-term prevalence of NDI (occurring from 1 year) among extremely preterm infants born at gestational age (GA) ≤28 weeks. Results: Of 2406 articles identified through searches, 69 met the protocol NDI definition (24 North America, 25 Europe, 20 Rest of World). Prevalence of any severity NDI in North America was 8%–59% at 18 months to 2 years, and 11%–37% at 2–5 years; prevalence of moderate NDI in Europe was 10%–13% at 18 months to 2 years, 3% at 2–5 years, and 9%–19% at ≥5 years; prevalence of any NDI in Rest of World was 15%–61% at 18 months to 2 years, and 42% at 2–5 years (no North America/Rest of World studies reported any NDI at ≥5 years). A trend toward higher prevalence of NDI with lower GA at birth was observed. Conclusions: Extreme prematurity has a significant long-term worldwide impact on neurodevelopmental outcomes.